Playing An Effective Diagnostic And Therapeutic Means - For People With Special Needs Deaf Child Model- - Bouaza, Salah; Boudari, Azeddine (جامعة الوادي - University of Eloued, 2022)
Playing therapy is fairly a new field of psychology for the study of human behaviour and it is true that there are various entrances and walks to study this behaviour. However, this field of many aspects has proven its effectiveness and its effect especially with troubled children and the techniques or treatment techniques and tools play a major role in the therapeutic process, the intrinsic values of the therapist permeate the relationship between him and the client and intervene to a large extent in determining the effects Therapeutic method of treatment. Play is a vital requirement for the good life of our children and daughters in successive stages of childhood, its importance for food and education This is a true saying all honesty (Clark Mustax, 1990 p. 11), that playing for children is a vital process in the way of growth and has brought to the attention of researchers that children spend a long time in Play what exactly is it about playing? After having long been searched in the end that play is the free activity that exercises itself and not to achieve any practical goal, play a major role in diagnosis and psychotherapy for people with special needs deaf child model. Keywords: Playing-Diagnosis-Treatment-Means-effective- deaf child.
article
Keywords: Playing, Diagnosis, Treatment, Means, effective, deaf child